Peran Pendamping SEKAMI dalam Membina Iman Anak di Stasi Santo Romanus Sifaoroasi Lolohowa - Martina Rosmaulina Marbun; Raimon Bawamenewi (Jurnal Magistra, 2025)
Faith is the basic attitude of man to welcome God who reveals Himself to man. SEKAMI faith building activity is an activity to build children's faith so that the child's faith is more firm and knows God better. SEKAMI companions are messengers of Allah to proclaim His word for SEKAMI children. The purpose of this paper is to find out how the role of SEKAMI companions in fostering children's faith at the Saint Romanus Sifaoroasi Simanaere Lolohowa Station. This study uses a qualitative method with an observation and interview approach. The data obtained will be analyzed and described narratively by referring to several books, related articles. The findings of this study are found that SEKAMI Companions play a very important role in fostering the faith of children at the Saint Romanus Sifaoroasi Simanaere Lolohowa Station. This is reflected in the personality of SEKAMI's companion who is close to Jesus and becomes a friend to SEKAMI's children.